Characterization of aquatic activities in the VRAEM area and its environmental impact - Ramírez Caján, Alfonso (2022)
The objective of this research was to characterize the aquatic activities that take place in the Vraem area; as well as to identify the environmental liabilities and sources of anthropic contamination on the banks and marginal strips adjacent to the rivers, caused by the formation of urban drains due to the lack of wastewater treatment plants and sewage and drainage networks; accumulation and clogging of solid waste from water transport, houses and riverside food stalls, leachate from drug maceration ponds inserted into rivers by runoff and percolation, and sedimentation and soil erosion by extraction of alluvial material. The methodology was based on the execution of a non-experimental investigation, with the collection of data in the field from observation and measurement tools. A total of 297 boats and 86 chimpanzee-type riverboats were registered, navigating the main rivers of the Vraem in the jurisdictions of Pichari, Ivochote, Boca Anapati, Quiteni, Puerto Ocopa, Camisea and Mantaro, 67 embarkation and disembarkation areas for personnel and material, 15 river transport companies and 8 shipyards dedicated to the construction and repair of naval steel material ships, describing their technical characteristics and their structuring process, concluding that although water transport allows interconnection and development socioeconomic in the Vraem area, the lack of education and inadequate management in this activity generates a significant negative impact for the environmental components.